Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.2310/7070.2005.4038
|View full text |Cite
|
Sign up to set email alerts
|

Reovirus Salvage of Positive Resection Margin: A Novel Treatment Adjunct

Abstract: Hypothesis:We hypnthesized tbat the use of teoviriis as an intraoperativc adjunct would improve local contri)! of positive margins in a human squamous cell carcinotna nude mouse model.Purpose: Tbis study was designed to (1) develop a nude mouse bumaii squamous cell carcinoma positive margin model and (2) assess tbe effect of adjunct intraopctativc treatment with reovirus irrigation and injection nn local conttoj of resections witb positive margins. Materials and Methods:We developed a positive margin nude mous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Reovirus was first shown to have an oncolytic effect in head and neck cancer cells by Ikeda et al [ 22 ] using in vitro and in vivo models. This effect has been demonstrated in numerous head and neck cell lines [ 24 , 25 , 36 , 37 ]. The oncolytic effect is believed to be independent of epidermal growth factor receptor (EGFR) activation and molecular predictors of response have yet to be identified [ 25 ].…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Reovirus was first shown to have an oncolytic effect in head and neck cancer cells by Ikeda et al [ 22 ] using in vitro and in vivo models. This effect has been demonstrated in numerous head and neck cell lines [ 24 , 25 , 36 , 37 ]. The oncolytic effect is believed to be independent of epidermal growth factor receptor (EGFR) activation and molecular predictors of response have yet to be identified [ 25 ].…”
Section: Discussionmentioning
confidence: 88%
“…Preclinical studies have shown the effectiveness of a combination of reovirus, paclitaxel and cisplatin in head and neck cancer lines [ 24 ]. Also, animal models have suggested a role for reovirus as an adjunct in surgically resected disease with positive margins [ 37 ]. Intravenously administered reovirus in combination with carboplatin and paclitaxel has been shown to have activity in advanced stage and recurrent head and neck cancer in a recently published phase I/II clinical trial [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation